2011
DOI: 10.3801/iafss.fss.10-693
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of Huge Oil Depot Fires - Generation of Fire Merging and Fire Whirl in (7 x 7) Arrayed Oil Tanks

Abstract: One of the largest industrial fire disasters may occur in oil tank depots which store large amounts of oil. Many previous studies on the fire safety of oil tank depots have been related to the fire propagation from one single oil tank fire to the adjacent tank via radiation. However, single oil tank fire may cause a fire whirl in windy conditions, entraining much more ambient air and enhancing flame radiation, which may increase the possibility of fire propagation toward the neighboring tanks. In addition, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…So, this helps use to figure out the importance of landuse zonal variances. Most of the studies regarding accidental fire breakdown of oil depots (Shi et al, 2014;Abbasi et al, 2014;Lin et al, 2012;Satoh et al, 2011) mainly concentrate on the structural design or management system of the oil depots i.e. they mainly try to determine the risk of fire breakdown inside the depots and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…So, this helps use to figure out the importance of landuse zonal variances. Most of the studies regarding accidental fire breakdown of oil depots (Shi et al, 2014;Abbasi et al, 2014;Lin et al, 2012;Satoh et al, 2011) mainly concentrate on the structural design or management system of the oil depots i.e. they mainly try to determine the risk of fire breakdown inside the depots and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…the largest distance between two fires where flame merging is observed, was reported to increase with an increase in heat release rates of individual pool fires. Later, Satoh et al (2011) conducted a computational fluid dynamics (CFD) based analysis on flame interactions from oil depot fires and observed the creation of a negative pressure zone at the centre of the merged fire. They concluded that this negative pressure is the cause of larger horizontal indrafts of ambient air, which in turn are the reason for the increase in the overall flame height.…”
Section: Introductionmentioning
confidence: 99%